Réponses

2014-05-06T23:55:43+02:00
Bonsoir,

simplifier ?
X=x+2+2x+3x+4x+............................+39x 

X = (x + 2x + 3x + 4x + ... + 39x) + 2

x + 2x + 3x + 4x + ... + 39x est la somme de 39 termes d'une suite arithmétique de raison x et dont le 1er terme est x et le 39ème terme est 39x.

x + 2x + 3x + 4x + ... + 39x =39\times\dfrac{x+39x}{2}\\\\x + 2x + 3x + 4x + ... + 39x =39\times\dfrac{40x}{2}\\\\x + 2x + 3x + 4x + ... + 39x =39\times20x\\\\x + 2x + 3x + 4x + ... + 39x =780x

Par conséquent
X = (x + 2x + 3x + 4x + ... + 39x) + 2
X = 780x + 2